Status of soil degradation in State of Uttar Pradesh - ARORA, SANJAY; SINGH, B. P. (Journal of Soil and Water Conservation, 2020)
Uttar Pradesh with a total area of 24.09 million ha is the India’s fifth largest state in terms of land area with a population of about 200 million and population density of 830 people per km2. Agriculture is the leading occupation in the state dependent on 16.8 million ha of cultivated land. Nearly 52.12 percent of the total geographical area in the state is affected by various soil degradation problems induced mainly by human-intervention. The most serious problem is of water erosion, causing loss of top soil and/or terrain deformation and has affected 11.39 m ha representing 38.69 percent area including ravenous lands along the rivers, wind erosion has been observed in 2.12 m ha, representing 0.72 percent of the total geographical area. About 4.65, 0.72 and 7.98% of the area of the state is affected by soil salinization or sodification, wind erosion and flooding, respectively.